Oorlog en ongelijkheid op zee en overzee - Odegard, Erik (TSEG - The Low Countries Journal of Social and Economic History, 2025)
This brief article discusses prof. Marjolein ‘t Hart’s recent book Oorlog en ongelijkheid, focusing on her analysis of the war at sea and outside of Europe. In her treatment of these two topics, ‘t Hart makes a number of valuable interventions in the debate, and raises some new questions. The argued efficiency of the Republic’s navy is a matter that requires more scholarly work. ‘t Hart argues cogently for a reassessment of the WIC. For while the company would be a military failure, it made a valuable contribution to the overall war effort of the Dutch Republic.